Signals of interstitial lung disease with novel antineoplastic agents in ovarian cancer: a three-database disproportionality study - Yang, Chenguang; Song, Xuan; Sun, Hongmei; Chen, Min; Chen, Xi; Liu, Chengjiang; Wang, Zhongjian; Zhu, Xialing (Frontiers in Pharmacology, 2026)
ObjectiveEmerging evidence suggests that certain antitumor drugs may be associated with interstitial lung disease (ILD); however, large-scale real-world data remain limited. This study aimed to identify disproportionate reporting signals of ILD associated with novel antineoplastic agents used in ovarian cancer.MethodsData from the US Food and Drug Administration Adverse Event Reporting System (FAERS; 2015 - Q1 2025), the Canada Vigilance Adverse Reaction Database (CVAR; 1965 - November 2024), and the Japanese Adverse Drug Event Report Database (JADER; 2004 - Q3 2024) were analyzed. Reports involving FDA-approved novel antineoplastic agents for ovarian cancer were included. Bayesian disproportional analysis was conducted to generate the proportional reporting ratio (PRR), reporting odds ratio (ROR), and information component (IC) to detect signals.ResultsEventually, 4,089 eligible records were retrieved, in which 2,783 ILD reports were from FAERS, 334 from CVAR, and 972 from JADER. Three drugs exhibited significant ILD reporting signals in FAERS: olaparib (ROR = 3.43, IC025 = 1.41), bevacizumab (ROR = 1.51, IC025 = 0.34), and mirvetuximab soravtansine-gynx (ROR = 4.27, IC025 = 1.40). Olaparib also showed ILD signals in CVAR (ROR = 3.43, IC025 = 0.73) and JADER (ROR = 1.55, IC025 = 0.26). Notably, mirvetuximab soravtansine-gynx associated ILD had the highest death constituent ratio (29.41%, 5/17). Compared to chemotherapy drugs, mirvetuximab soravtansine-gynx and olaparib demonstrated stronger associations with ILD.ConclusionPatients with ovarian cancer administrating mirvetuximab soravtansine-gynx or olaparib merit close monitor for ILD. Early detection and immediate intervention are critical.